2022
DOI: 10.1186/s12868-022-00746-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of kynurenine pathway between inflammation and glutamate in the underlying etiopathology of CUMS-induced depression mouse model

Abstract: Inflammation and glutamate (GLU) are widely thought to participate in the pathogenesis of depression, and current evidence suggests that the development of depression is associated with the activation of the kynurenine pathway (KP). However, the exact mechanism of KP among the inflammation, GLU and depression remain poorly understood. In this study, we examined the involvement of KP, inflammation and GLU in depressive phenotype induced by chronic unpredictable mild stress (CUMS) in C57B/6 J mice. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Our finding was further supported by a preclinical study that denoted increased IDO expression in the nucleus accumbens, hippocampus, and hypothalamus of PSD-like phenotype mice (29). There are several underlying mechanisms that may account for the association of IDO1 with PSD: the elevated levels of proinflammatory cytokines after stroke upregulate IDO1 expression that causes the depletion of serotonin precursor tryptophan and increased neurotoxic kynurenine metabolite (quinolinic acid), an agonist of NMDA receptors, leading to the occurrence of depression (14,(30)(31)(32). IDO1 has been seen as a central hub linking immuneinflammatory processes to the monoaminergic (33) and glutamatergic systems implicated in depression (14).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our finding was further supported by a preclinical study that denoted increased IDO expression in the nucleus accumbens, hippocampus, and hypothalamus of PSD-like phenotype mice (29). There are several underlying mechanisms that may account for the association of IDO1 with PSD: the elevated levels of proinflammatory cytokines after stroke upregulate IDO1 expression that causes the depletion of serotonin precursor tryptophan and increased neurotoxic kynurenine metabolite (quinolinic acid), an agonist of NMDA receptors, leading to the occurrence of depression (14,(30)(31)(32). IDO1 has been seen as a central hub linking immuneinflammatory processes to the monoaminergic (33) and glutamatergic systems implicated in depression (14).…”
Section: Discussionsupporting
confidence: 79%
“…There are several underlying mechanisms that may account for the association of IDO1 with PSD: the elevated levels of proinflammatory cytokines after stroke upregulate IDO1 expression that causes the depletion of serotonin precursor tryptophan and increased neurotoxic kynurenine metabolite (quinolinic acid), an agonist of NMDA receptors, leading to the occurrence of depression (14,(30)(31)(32). IDO1 has been seen as a central hub linking immuneinflammatory processes to the monoaminergic (33) and glutamatergic systems implicated in depression (14). Our results, taken together, supported that the interactions of cytokine-serotonin and -glutamate via IDO1 could play a key role in PSD (3, 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with observed sex differences in TRP metabolism during pregnancy in previous animal models with chronic stress. 49 , 50 Finally, we observed differences in salivary KYNA concentrations between mothers with higher and lower levels of trauma in male pregnancies. To the best of our knowledge, no studies have reported such sex-specific differences.…”
Section: Discussionmentioning
confidence: 57%